Pragmatics in Contested Interpretation: Varied Audiences, Varied Implicatures, Varied Inferences - Bourgeois, Samuel; Bousfield, Derek (Springer Nature Switzerland, 2026)
This open access book explores the mechanisms by which different audiences hearing the same comments made by the same speaker in the same context come to different interpretations as to the meanings behind them. The study uses a ‘pragmacognitive’ approach that fuses insights from sociopragmatics and critical discourse analysis to examine both the speaker’s intentions and the audience’s reactions. The authors explore the role and construction of context through a pragmacognitive analysis of two controversial utterances made by Donald Trump during the 2020 and 2024 presidential election campaigns and one controversial comment from President Joe Biden’s short-lived 2024 re-election campaign. They analyse in detail how these comments have been interpreted by those receiving their words within the wider political context of a highly politicised and divisive campaign, inferred by some to constitute problematic insulting behaviours and/or calls for violence while others have found them to be playful political critiques. The authors emphasise how indeterminate language, activity type conventions, and the respective identities and reality paradigms of the speakers contribute to creating varied audiences with ‘contested interpretations’. Contested interpretations are particularly apparent in cases where ambiguous, hyperbolic, or even metaphorical language is used to simultaneously conduct face-attack against individuals and organizations, and appeal to a political base of supporters. This book contributes to the growing body of scholarship in this area and will be of interest to a multidisciplinary audience including readers in linguistics, political rhetoric, and political discourse.
Keywords: context; implicature; audience; interpretability; humour; reality paradigms